2020
DOI: 10.3390/biom10091218
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae and Lipid Rafts in Endothelium: Valuable Organelles for Multiple Functions

Abstract: Caveolae are flask-shaped invaginations of the plasma membrane found in numerous cell types and are particularly abundant in endothelial cells and adipocytes. The lipid composition of caveolae largely matches that of lipid rafts microdomains that are particularly enriched in cholesterol, sphingomyelin, glycosphingolipids, and saturated fatty acids. Unlike lipid rafts, whose existence remains quite elusive in living cells, caveolae can be clearly distinguished by electron microscope. Despite their similar compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 157 publications
(166 reference statements)
0
33
0
Order By: Relevance
“…Furthermore, at the cellular level, rafts and related membrane microdomains, such as caveolae, characterized by a high expression of caveolin-1, have been proposed to play important roles in the sorting of membrane and non-membrane molecules (Browne and London, 2000 ; Parton and Richards, 2003 ). In fact, the study of caveolar platform has been proposed as a potential target to inhibit the entry of SARS-CoV-2 (Filippini and D'Alessio, 2020 ).…”
Section: Lipid Raftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, at the cellular level, rafts and related membrane microdomains, such as caveolae, characterized by a high expression of caveolin-1, have been proposed to play important roles in the sorting of membrane and non-membrane molecules (Browne and London, 2000 ; Parton and Richards, 2003 ). In fact, the study of caveolar platform has been proposed as a potential target to inhibit the entry of SARS-CoV-2 (Filippini and D'Alessio, 2020 ).…”
Section: Lipid Raftsmentioning
confidence: 99%
“…Alternatively, a caveolae-dependent pathway may be used. Caveolae are small invaginations of the plasma membrane that are composed of cholesterol, glycosphingolipids, and caveolin (Filippini and D'Alessio, 2020 ). Caveolin is able to oligomerize, leading to the formation of caveolin-rich microdomains in the plasma membrane, and subsequently, the caveolar vesicles may fuse with the early endosomal compartment.…”
Section: Lipid Raftsmentioning
confidence: 99%
“…The purpose of the present study was to explore the role of Cav-1 in peripheral sensitization, starting with the alterations of the peripheral incision tissue. The caveolae are a special form of lipid raft, which is a small invagination of the plasma membrane that is present in a number of mammalian cells, such as endothelial cells, adipocytes and skeletal muscle ( 27 , 28 ). Previous studies have reported that caveolae are the cellular center of signaling molecules ( 9 , 10 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some recognition receptors for viruses, including coronavirus, cluster into lipid rafts [ 7 ]. Thus, lipid platforms are considered as potential targets to block virus entry into endothelial cells [ 8 ].…”
Section: Lipid Raftsmentioning
confidence: 99%